Archaeological Perspectives on Scott's Against the Grain: A Deep History of the Earliest States. Issue 4 (November 2019) - Leppard, Thomas P.
Abstract : James C. Scott's Against the Grain has immense relevance for how archaeologists view the dynamics of early states and complex polities. In this volume, Scott—already established as a leading theorist of states and statecraft (e.g. Scott 1997; 2009)—brings his analytic power and capacity to turn a phrase to bear on the topic of the 'earliest states'.